Halal assurance at farm level in the poultry supply chain - Ramli, Mohd Hasli; Rosman, Arieff Salleh; Md Sikin, Adi; Jamaludin, Mohammad Aizat; Ajmain, Muhammad Talhah (Academic Inspired Network, 2020)
Halal Assurance System (HAS) develop by JAKIM has undergone several revisions in its requirement since 2011. HAS is currently practised at the downstream of poultry supply chain focusing only on the slaughtering and production stage of chicken products. Despite of the importance and significance to comply the HAS’s halal critical point (HCP) at each step in poultry processing industry, there are still limited studies emphasizing the HAS the implementation at the upstream level. Thus, this study focuses on the qualitative methodology approach through documentation analysis to obtain sources of information on the importance of HAS and the elements of halal risk control (HRC) in broiler chicken farm activities. Finding shows that there are five elements in the broiler chicken farms that have been identified as HRC includes livestock food and drink, medical, farm biosecurity, infrastructure, and logistics. So, implementing of HAS in the broiler chicken farm is important to maintain the transparency and integrity of halal certification policies in the HRC at the upstream level of halal food supply chain. This study also suggested that HAS can be applied on other livestock sectors such as ruminant and fish for safeguarding the halal status of meat supply chain in Malaysia.